Public health challenges after the February 6 earthquakes: A comprehensive review of immediate and long-term impacts in Turkiye - Kocer, Anil Tevfik; Akpek, Ali; Vural, Alperen; Aslan, Ayca; Erkoc, Arzu; Ozen, Aybike Manav; Sahin, Aynur; Oktay, Aysel; Senol, Ayse Asli; Batioglu-Karaaltin, Aysegul; Demir, Azize; Inan, Benan; et al. (ELSEVIER, 2024)
Earthquakes are one of the most destructive natural hazards that cause loss of life, loss of property and destruction of infrastructure when they interact with vulnerabilities in human systems. The health impacts of these events are not only limited to immediate trauma and injuries, but also affect both physical and mental health in the short and long term. In this context, understanding the short- and long-term public health impacts of earthquakes and developing effective solutions is a priority both nationally and internationally. This review comprehensively examines the health challenges posed by earthquakes, focusing on the earthquakes that occurred in Turkiye on February 6, 2023. It addresses acute responses such as post-earthquake trauma management, emergency health services, potential earthquake-related risks and search and rescue activities, as well as chronic challenges such as sustained physical rehabilitation and psychosocial support in the long term. By analyzing current strategies and outcomes, this study aims to provide important insights into effective health management practices following earthquakes.
Keywords: Kahramanmaras earthquake; Source of health risks; Mental health; Long-term health impacts; Natural hazards and vulnerabilities; RISK; RESILIENCE; EXPOSURE; HAZARDS; TRAUMA; FAULT; ZONE; SEA; Geology; Meteorology & Atmospheric Sciences; Water Resources